Pengaruh Program Parenting terhadap Pengetahuan dan Sikap Orang Tua dalam Pemenuhan Kebutuhan dasar Anak Usia Dini - Triana Setijaningsih; Wiwin Matiningsih (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2014)
Parenting Program is a program that allows the alignment between sustainability and education conducted in educational institutions and is done at home. The purpose of research was to analyze the effect of parenting program toward knowledge and attitude of parent for giving fundamental  needs of children in early age. Method: Research was pre-post test Design. The population and sample was one of the parents PAUD Sabana Blitar that lead to inclusion criteria as many as 43 respondents with a purposive sampling technique. Data was analyzed by descriptive and inferential using the Wilcoxon signed rank test and McNemar test with SPSS 17 for window, the level of significance (p ≤ 0.05). Result: The result of research got the value of P = 0.000 (Wilcoxon signed rank test), which means there was  effect of Parenting program toward parent's knowledge, and P = 0.016 (McNemar Test) which means that there was effect of Parenting Program for parent's attitude. Discussion: Parenting Program is perceived very beneficial by parents as a complement of parenting in PAUD and at home, it is necessary to proceed more intensive and varied.